Mandating teaching approaches stifles innovation: a case against - Luqman Baehaqi (Institut Agama Islam Negeri (IAIN) Palangka Raya, Indonesia, 2022)
The article discusses the primacy of Systemic Functional Linguistics (SFL) in research and pedagogy on second language (L2) writing in Indonesia. Indonesian academics use SFL theory as a shell to value arguments and observations in the methodological literature of L2 writing, demonstrating how the theory transforms into an